Silicate Fertilizer Amendment Alters Fungal Communities and Accelerates Soil Organic Matter Decomposition - Das, Suvendu; Lee, Jeong Gu; Cho, Song Rae; Song, Hyeon Ji; Kim, Pil Joo (Frontiers in Microbiology, 2019)
Soil microorganisms play a crucial role in organic matter decomposition and nutrient cycling in cropping systems. Compared to bacteria, fungal community composition and the role of fungi in organic matter decomposition and nutrient cycling in agro-systems are, however, elusive. Silicon (Si) fertilization is essential to improve agronomic performance of rice. The effects of the Si fertilizer application on the soil fungal community composition and their contribution in soil organic matter decomposition are not yet studied. We investigated the short-term (120 days) slag silicate fertilizer (SSF) amendment impacts on plant photosynthesis and soil biochemical changes, soil fungal communities (assessed by ITS amplicon illumina sequencing), hydrolytic and oxidase enzyme activities, CO2 emissions, and bacterial and fungal respiration in diverse eco-geographic races of rice (Oryza sativa L.), i.e., Japonica rice (O. sativa japonica) and Indica rice (O. sativa indica). The short-term SSF amendment significantly increased the relative abundance of saprotrophic fungi and accelerated organic matter decomposition. The increase in saprotrophic fungi was mostly attributed to greater labile C availability and Si availability. Higher organic matter decomposition was accompanied by an increase in both hydrolytic and oxidative enzyme activities in response to the SSF amendment. The stimulation of oxidative enzyme activities was explained by an increase in root oxidase activities and iron redox cycling, whereas stimulation of hydrolytic enzyme activities was explained by the greater labile C availability under SSF fertilization. We conclude that the short-term SSF amendment increases saprotrophic fungal communities and soil hydrolytic and oxidative enzyme activities, which in turn stimulates soil organic matter mineralization and thus could have negative feedback impacts on soil C storage in submerged rice paddies.